TINJAUAN HUKUM ISLAM TERHADAP PERAN MUSLIMAH ENTREPRENEURSHIP DALAM PENINGKATAN PEREKONOMIAN SYARI’AH Studi Kasus di Komunitas Pengusaha Muslimah (Kopami) Jombang - Azizah, Ninik; Azizah, Fitrotul (Irtifaq, 2020)
This article aims to determine the view of Islamic law on Muslimah entrepreneurship in improving the Islamic economy in the Jombang independent entrepreneur community. Using a qualitative approach to the type of field research, data from interviews, observations and documentation that are analyzed decuctively by taking theories, arguments about Islamic law on the role of Muslimah entrepreneurship in improving the Islamic economy, then the theory is drawn on the reality or facts of cases in the field. The results showed that the majority of Kopami members are Muslim women while carrying out their role as a career Muslimah or entrepreneurship does not violate the provisions of Islamic law. Meanwhile, the role of Muslimah entrepreneurship in Kopami is able to improve the Islamic economy in the family and society. Keywords: Islamic Law, Role of Muslimah, Entrepreneurship, Islamic Economic Law.